(untitled) (Journal of human and social sciences, 2023)
This study attempted to evaluate the extent to which Libyan universities are committed to and interested in training their faculty members, especially in educational aspects that would enhance the quality of university outputs. Using the University of Gharyan as a model, the study found a lack of sufficient awareness regarding the importance of training as a fundamental element in improving the efficiency of university professors and enhancing their ability to perform effectively. This is clearly evident from the high percentage of faculty members included in the study who had not undergone any training programs.